Low-intensity daily smoking and cause-specific mortality in Mexico: prospective study of 150 000 adults - Thomson, B; Tapia-Conyer, R; Lacey, B; Lewington, S; Ramirez-Reyes, R; Aguilar-Ramirez, D; Gnatiuc, L; Herrington, WG; Torres, J; Trichia, E; Wade, R; Collins, R; et al. (Oxford University Press, 2021)
Background Research is needed to determine the relevance of low-intensity daily smoking to mortality in countries such as Mexico, where such smoking habits are common.